ARGUMENTS IN FAVOR OF INTRODUCING THE GLOBAL CORPORATE MINIMUM TAX - Daniela PÎRVU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2021)
In recent years, the multinational corporations have developed increasingly sophisticated and refined tax avoidance tax planning practices. As a result of these practices, many governments and international institutions have called for a reduction in tax bases and proposed various measures, which resulted in an agreement in 2021, which provided the introduction of the global corporate minimum tax. This paper presents a number of arguments in favor of introducing this measure by analyzing the literature and empirical research on the taxes paid by the multinational corporations.